BAHASA DALAM UPACARA LARUNG, SEDEKAH LAUT DI LAUT BONANG, KECAMATAN LASEM, KABUPATENREMBANG, JAWA TENGAH - Rahmah Purwahida, Bakhtiar Dwi Yunika, dan Dhany Nugrahani A. (Pelita - Jurnal Penelitian Mahasiswa UNY, 2008)
This research is intended to describe the form, meaning, and the background ofthe use of language in the Larung Ceremony prayer, Bonang beach offering 2003. Thesubjects of this research are modin (village religious functionary), society, and ceremonyparticipants. The technique of collecting data was carried out by having observation,interview, and documentation. The research instruments were the researcher herselfwith some other instruments such as CD, MP3, camera and field note. The techniqueof data analysis was inductive while the data validity used triangulation.Larung ceremony, Bonang Beach Offering 2003, uses the language reflecting theculture of this region. Culture influences the way of thinking and the attitude of BonangBeach people in using the language, especially when the modin reads the spell of RajahKala Cakra while doing larung. The use of spell reflects the culture of Bonang Beachpeople who were still in Kejawen at that time and believed in the existence of Northbeach ruler.The spell read by the modin is a prayer used to chase any kinds of evil magic thatdisturbs the peace of the fisherman community and in order to get god-given right byhaving abundant sea crop. The symbol completes all aspects of human life, includingthe cultural aspect such as behavior and knowledge. The tradition of doing beach offeringwith various offerings represents certain symbols. Generally Javanese assume thesymbols with the same meaning, only places and kinds of ceremony which are different.Key words: language, larung, beach offering, Bonang